Growth and transport properties of Mg3X2 (X = Sb, Bi) single crystals. (December 2018) - Xin, J.; Li, G.; Auffermann, G.; Borrmann, H.; Schnelle, W.; Gooth, J.; Zhao, X.; Zhu, T.; Felser, C.; Fu, C.
Abstract: The discovery of high thermoelectric performance in n -type polycrystalline Mg3 (Sb, Bi)2 -based Zintl compounds has ignited intensive research interest. However, some fundamental questions concerning the anisotropic transport properties and the origin of intrinsically low thermal conductivity are still elusive, requiring the investigation of single crystals. In this work, high-quality p -type Mg3 Sb2 and Mg3 Bi2 single crystals have been grown by using a self-flux method. The electrical resistivity ρ of Mg3 Bi2 single crystal displays an anisotropy with ρ in-plane twice larger than out-of-plane. The low-temperature heat capacity and lattice thermal conductivity of Mg3 Sb2 and Mg3 Bi2 single crystals have been investigated by using the Debye–Callaway model, from which the existence of low-lying vibration mode could be concluded. Large Grüneisen parameters and strong anharmonicity are found responsible for the intrinsically low thermal conductivity. Moreover, grain boundary scattering does not contribute significantly to suppress the lattice thermal conductivity of polycrystalline Mg3 Sb2 . Our results provide insights into the intrinsic transport properties of Mg3 X 2 and could pave a way to realize enhanced thermoelectric performance in single-crystalline Mg3 X 2 -based Zintl compounds. Graphical abstract: Mg3 X 2 ( X  = Sb, Bi) single crystals have been successfully grown from a self-flux method. It is found that Mg3 Bi2 displays anisotropic electrical resistivity along the b and c axis. The lattice thermal conductivity of polycrystalline Mg3 Sb2 is only 15% lower than that of its single crystal, indicating that grain boundary scattering does not significantly contribute to suppress the phonon transport. PR, resonant scattering. Highlights: High-quality Mg3 X 2 ( X  = Sb, Bi) single crystals have been successfully grown from a self-flux method. The electrical resistivity ρ of Mg3 Bi2 single crystal displays an anisotropy with ρ in-plane twice larger than out-of-plane. Large Grüneisen parameters and strong anharmonicity are found responsible for their intrinsically low thermal conductivity. Grain boundary scattering contributes insignificantly to suppressing the lattice thermal conductivity of Mg3 Sb2 .